The Role of Bhabinkamtibmas in Preventing Radicalism in the Legal Area of ​​the Cirebon City Police - Fabel, Heraldy Yudhantara (Indonesian Journal of Police Studies, 2024)
In the last 20 years, the understanding and movements of radicalism in all corners of the world, especially in Indonesia have become increasingly disturbing and alarming. The flow of information in the 4.0 era and the rapid technological advancements made radicalism movements and understandings develop rapidly and globally. Its actions which emphasize acts of violence against people who disagree respond as pro-violent radicalism and intolerance. In order to understand the role of Bhabinkamtibmas in opposing radicalism, understanding the role of Bhabinkamtibmas in opposing the understanding of radicalism in the Cirebon City Police jurisdiction, the authors use social differentiation theory, role & status theory, relationship theory, and management theory. This study uses qualitative with semi-structured interviews. The location of the study was conducted in the jurisdiction of the Cirebon City Police. Data analysis in using this uses the results of structured and unstructured interviews, collection and documentation data obtained from relevant sources. Bhabinkamtibmas in preventing the understanding of radicalism in the Cirebon City Police jurisdiction is ongoing so far lacking in support of special budgets, none of which is financed with funds from involved parties, and human resources that cannot be accounted for in every Polsek in the Cirebon City Police jurisdiction. For this reason, no-no-management, in opposing right groups, needs more attention, reforming and mutating members of the Bhabinkamtibmas related to the budget, carried out by testing the appropriateness and appropriateness of interests and abilities in carrying out tasks such as Bhabinkamtibmas, can be used to increase the de-radicalization and deepening of radical notions so as to prevent the problem in the community.